The Effect of Catalyst Amount and Time on the Results of Converting Rubber Wood Chip Waste by Catalytic Pyrolysis into Alternative Energy - Patrio, Aditia; Rusnadi, Irawan; Syarif, Aida (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
In the rubber plantations of South Sumatra, covering an area of 1,013,969 hectares, there exists an underutilized waste stream known as rubber wood waste. This waste can be subjected to pyrolysis to Yield char, bio-oil, and syngas products. This research is centred on pyrolyzing rubber wood waste, employing various zeolite catalysts and time durations, to explore the potential of alternative energy sources and calculate the Specific Energy Consumption (SEC). The pyrolysis results, with variations in catalysts and time, indicate that the optimal combination is at a temperature of 390°C, using 6% zeolite catalyst, and a duration of 70 minutes. The resultant Yields comprise char at 21.73% with a calorific value of 6264.87 kcal/g, bio-oil at 22.50%, and syngas at 45.28% with a CH4 content of 55.52%. The most SEC-optimal variation is at a temperature of 390°C, using a 6% zeolite catalyst, and 30 minutes, with an SEC value of 3.25 kWh/L.